Évaluation des conséquences d’aménagements d’infrastructures sur les déplacements d’animaux. Définition et expérimentation d’un modèle de simulation agent - Laurence Jolivet; Marianne Cohen; Anne Ruas (Cybergeo, 2015)
Landscape elements influence fauna movements. The information is collected so that to identify obstacles and interesting corridors: locations of animals and topographical databases describing the spatial environment. The aim of this research is to simulate fauna movement into spatial areas, both in a real context then in a context modified by infrastructures. We start by analyzing the collected movement data and the influence of landscape elements on three species: the red fox, the roe deer and the red deer. The perception of space is different, depending on the species and on the type of environment. As an example, wooded area can be either used for resting or foraging. Then the results of data analyses and knowledge on the species are integrated in a simulation model based on agents. Trajectories are built by taking into account the spatial behavior of species and the characterization of both obstacles and movement corridors. We finally test the simulation process on a modified area with a road and wildlife infrastructures. We assess the consequences on movements. The model tends to confirm the barrier effect of the motorway even if the effect is reduced by ecological corridors. While the road limits animals’ movements, the corridor favors spatial accessibility and leads to crossings at precise locations. These results highlight the interest of a model in order to assess the efficacy of wildlife preservation such as the measure of “Trame verte et bleue”.